Learning geometry and visuo-spatial abilities through coding - Martina Sabatini (Firenze University Press, 2016)
This paper deals with the theme of coding, focusing particularly on its introduction in a specific primary school curriculum. The work presents the PhD research project "Learning geometry and visuo-spatial abilities through coding". The project, which is not yet concluded, aims to reflect on the possibility of introducing coding activities within the primary school curricula of geometry of third graders, in order to study if and how these activities affect learning geometry and visuo-spatial abilities. To do so, the processes of teaching and learning of experimental classes (those in which coding activities take place) and control classes (those in which coding activities do not take place) will be compared, both in terms of quantity and quality. The classes has been chosen according to a uniformity requirement with respect to the starting points of geometrical knowledge and visuo-spatial abilities.   L'apprendimento di conoscenze geometriche e abilità visuo-spaziali attraverso il coding Il presente lavoro affronta la tematica del coding focalizzandosi in particolar modo sulla sua introduzione in uno specifico curricolo di scuola primaria. Viene presentato il progetto di ricerca di dottorato "L'apprendimento di conoscenze geometriche e abilità visuo-spaziali attraverso il coding". Il progetto, non ancora concluso, intende riflettere sulla possibilità di introdurre attività di coding all'interno dei curricoli di geometria delle classi terze di scuola primaria, al fine di studiare se e come questo tipo di attività influisca sull'acquisizione di apprendimenti geometrici e abilità visuo-spaziali. Per farlo, verranno confrontati, sia in termini quantitativi che qualitativi, i processi di insegnamento-apprendimento di classi sperimentali (quelle in cui avvengono attività di coding) e di classi di controllo (quelle in cui non avvengono attività di coding). Le classi sono state scelte secondo un criterio di omogeneità relativamente alle situazioni di partenza delle conoscenze geometriche e abilità visuo-spaziali.